Use of a Torsion Pendulum Balance to Detect and Characterize What May Be a Human Bioenergy Field - Hansen, John Norman; Lieberman, Joshua A. (Journal of Scientific Exploration, 2013)
Whereas the concept of bioenergy fields is thousands of years old, their existence has never been verified by scientific experiments designed to detect and measure them; so bioenergy fields have no scientific credibility. The instruments used for those experiments typically detect components of the electromagnetic spectrum. The experiments presented here utilize a detector that instead is sensitive to actual “pushing” forces that are capable of altering the momentum of a physical object such as a simple torsion pendulum balance that is suspended above a seated human subject. The experimental design includes a videocamera connected to a computer that can detect and measure the pendulum movements with high precision, and store this information in a data file for later analysis. Experiments show that the pendulum detects and measures substantial forces that drastically alter the motions of the pendulum when a subject is seated under it. The following effects are consistently observed with every subject in every experiment performed up to now: 1) Substantial shifts of the center of oscillation of the pendulum; shifts as large as 2.2 cm (7 deg) requiring a force that is equivalent to 45 mg are observed, 2) Many new frequencies of oscillation of the pendulum are introduced when a subject is present, 3) Dramatic changes in the amplitudes of oscillation of the pendulum are observed throughout the experiment; increasing, decreasing, and increasing again, in patterns that resemble chemical relaxation processes, 4) These shifts of the center of oscillation, the new frequencies of oscillation, and the changes in amplitudes all persist for 30–60 min after the subject has left the pendulum. This is inconsistent with the physics of a simple harmonic oscillator such as a torsion pendulum, which should return to simple harmonic oscillation immediately after any exterior disturbances are discontinued. After conducting control experiments to rule out effects of air currents and other artifacts, it is concluded that the effects are exerted by some kind of force field that is generated by the subject seated under the pendulum. We know of no force, such as one within the electromagnetic spectrum, that can account for these results. It may be that a conventional explanation for these surprising results will be discovered, but it is possible that we have observed a phenomenon that will require the development of new theoretical concepts. For now, it is important that other investigators repeat and extend our observations.